Faktor Yang Memengaruhi Perilaku Merokok Pada Remaja Di SMA 2 Dan SMK 8 Muhammadiyah Tanjung Sari Kecamatan Medan Selayang - solihin; Mappeaty Nyorong; Nur’aini; Dian Maya Sari Siregar (Pusat Riset dan Inovasi Nasional, 2023)
Smoking behavior is something that someone does in the form of burning and smoking it and causing smoke that people around him can inhale. Smoking behavior is indeed difficult to avoid in adolescents, and this caused by several factors such as behavior that is still very difficult to change and the environment around adolescents. The aim of the study was to determine the factors that influence smoking behavior in adolescents at SMA 2 and SMK 8 Muhammadiyah Tanjung Sari, Medan Selayang District. The research design uses a quantitative method which is carried out by an analytical survey with a Cross Sectional Study approach. The population in this study were all male students at SMA 2 and SMK 8 Muhammadiyah, with a total of 559 students. The sample used the Purposive Sampling technique, as many as 85 male students. Data analysis used univariate, bivariate and multivariate analysis. The results showed that there was an influence of knowledge, beliefs, exposure to cigarette advertisements, the availability of cigarettes, the role of parents, the role of teachers, the role of peers on smoking behavior in adolescents at SMA 2 and SMK 8 Muhammadiyah Tanjung Sari, Medan Selayang District. While the most dominant factor is knowledge. The study concludes that all variables influence smoking behavior in adolescents at SMA 2 and SMK 8 Muhammadiyah Tanjung Sari, Medan Selayang District. It is suggested to the school to overcome smoking habits among adolescents that it is hoped that the school will conduct counselling about the dangers of smoking, implement KTR and carry out routine raids for smokers throughout the school environment.